ChemInform Abstract: Preparation and Use of Combustion‐Derived Bi2O3 for the Synthesis of Heterocycles with Anticancer Properties by Suzuki—Coupling Reactions. Issue 16 (April 2015) - Anusha, Sebastian; Anandakumar, B. S.; Mohan, Chakrabhavi Dhananjaya; Nagabhushana, G. P.; Priya, B. S.; Rangappa, Kanchugarakoppal S.; Basappa, Basappa; Chandrappa, G. T.
Abstract Bismuth oxide is synthesized via simple, rapid and energy efficient solution combustion synthesis by employing sucrose as a fuel.